APLIKASI PEMESANAN TRANSPORTASI LAUT WISATA PULAU DI KABUPATEN TAPANULI TENGAH BERBASIS WEB - Hasibuan, Sindi Anggreni; Yahfizham, Yahfizham; Aninda Muliani, Aninda (JISTech (Journal of Islamic Science and Technology), 2023)
Due to its potential for natural beauty, the island in Central Tapanuli Regency is currently one of the destinations to visit. Since so many people wish to visit the island, they unquestionably want some form of sea transportation, with a ship serving as one option for the voyage. Despite the abundance of marine transportation options, it is challenging for tourists to locate ships and learn when they depart. Based on this, it is important to create a website-based information system that serves as an online ship reservation and offers guidance on how to identify and book ships more quickly and easily utilizing the First In First Out (FIFO) algorithm, which schedules according to the queue. The first process to enter will be the first to run.